Yield evaluation of hybrid maize candidates with high productivity and drought tolerance - Majid, Royhan; Amzeri, Achmad; Chan, Caroline; Suhartono, Suhartono; Umam, Ahmad Syaiful (Agrovigor, 2025)
One solution to solve the problem of low maize productivity in dry land is to develop superior maize varieties with high production characteristics and resistance to drought stress.  This study aims to evaluate the characteristics of 10 hybrid maize candidates with high production characteristics and resistance to drought stress.The research used a Randomized Complete Block Design (RCBD) with 13 genotypes (10 hybrid maize candidates, three comparison varieties (Jakaring, Pioneer-X, and Bisi-X) as treatments and was repeated three times, so that there were 39 experimental units.Drought stress research follows the CIMMYT method. The observation parameters in this study were plant height, stem diameter, number of leaves, leaf length, leaf area, ear height, days of 50% tasseling, days to 50% silking, harvest age, number of kernel rows, weight of cob with husk, ear length, ear diameter, kernel width, kernel length, kernel thickness, 1000-kernel weight, and production per hectare. The results of the variance analysis showed that several genotypes tested had a significant effect on the characters of plant height, stem diameter, number of leaves, leaf length, leaf area, ear height, days of 50% tasseling, days to 50% silking, harvest age, number of kernel rows, weight of cob with husk, ear length, ear diameter, kernel width, kernel thickness, 1000-kernel weight, and production per hectare.  The value of heritability in the broad sense of candidate maize for all evaluated characters ranged from 0.00-97.64. The character of production per hectare significantly correlates with the ear length and ear diameter, with respective correlation coefficient values of 0.36 and 0.56.  The character of the ear height had a significant negative correlation with the production per hectare character, with a correlation coefficient value of -0.39.  The selected genotypes in releasing hybrid varieties were G1, G2, G3, G4, and G6.